Changing the Paradigm on Human Enhancements: The Special Case of Modifications to Counter Bone Loss for Manned Mars Missions. (May 2019) - Szocik, Konrad; Campa, Riccardo; Rappaport, Margaret Boone; Corbally, Christopher
Abstract: Among the greatest obstacles to the implementation of crewed space missions are human biological limitations. Difficulties were always envisioned in relation to both Earth's moon and Mars but more so for Mars because long spaceflights would also expose crew to prolonged microgravity conditions, in addition to radiation. The result could well be osteoporosis, bone fractures, and disability. In this article, we do not contest the validity of bone loss studies. Rather, we question a seemingly tacit assumption about the immutability of human nature. Indeed, new, invasive, and noninvasive techniques of human enhancement already allow humans to enjoy modifications that will enable lengthy space missions. The alteration of human DNA has not only aided cancer patients but, for example, by using the CRISPR/Cas9 genome editing procedure, can also help to prevent damage to limbs and joints that a prolonged Mars mission could cause for the crew. Possible ethical objections to this solution are discussed, and trade-offs between risks and benefits outlined.